Acute Anaerobic Exercise Affects the Secretion of Asprosin, Irisin, and Other Cytokines – A Comparison Between Sexes - Wiecek, Magdalena; Szymura, Jadwiga; Maciejczyk, Marcin; Kantorowicz, Malgorzata; Szygula, Zbigniew (Frontiers in Physiology, 2018)
Objective: The new adipokine, which is asprosin, affects glucose release from the liver to the blood, and thus, influences anaerobic exercise metabolism. This is the first study assessing whether single anaerobic exercise affects asprosin secretion in women and men. Methods: 10 men and 10 women (aged 21.64±1.22 and 22.64±1.49, respectively) performed a single 20-second bicycle sprint. Blood samples were collected before exercise and in the 3’, 15’, 30’ and 60’ of recovery, and 24 hours after competition. Results: Only in women did asprosin (P=0.001) (15’, 30’, 60’, and 24 hours after exercise) and irisin (P<0.001) (15’, 30’ and 60’) concentrations increase. Leptin, however, decreased (P=0.001) at 3’, 15’, and 30’ in women. There was an increase in interleukin-6 (P<0.001) at 3’, 15’, 30’ and 60’ of recovery in men, at 15’, 30’, 60’, and 24 hours of recovery in women, along with a simultaneous decrease in interleukin-1β (P<0.001) at 15’, 30’ and 60’ of recovery in men, and at 15’ and 30’ of recovery in women; (r=-0.35, P<0.001). There was a positive correlation between asprosin and adiponectin and a negative one between asprosin and leptin. The increase in irisin concentration at 30’ of recovery was positively correlated with the increase in asprosin concentration and percentage fat content, while being negatively correlated with total and lean body mass. Conclusion: The single anaerobic effort induced an increase in asprosin and irisin secretion while reducing leptin secretion in women. Adipocytokine concentration changes are inter-related. Regardless of sex, anaerobic efforts induce anti-inflammatory effects.